Electromagnetic scattering from an electrically dense vegetation medium - Ewe, Hong Tat; Chuah, Hean Teik (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2000)
A vegetation medium can generally be modeled. as a discrete random medium where scatterers such as disks, needles, and cylinders are used to represent the leaves, branches, and trunks. At low frequency, it is possible that the spacing between the scatterers is comparable or smaller than the wavelength. This medium is considered electrically dense, and the coherence effect from the scatterers indicates that the assumption of independent scattering of the scatterers is no longer valid. In addition, in a dense vegetation medium where the scatterers are close to each other, near field interactions should also be considered, In this paper, the coherence effect from the various correlated scatterers is taken into account by introducing the array phase correction to the phase matrices of the scatterers. For the near field interaction effect, both the Fresnel phase correction and the amplitude correction are considered. The Fresnel phase correction is incorporated by including the higher order terms in the phase of the scattered field from a scatterer, whereas the amplitude correction is obtained from the near field amplitude term of the scattered field, These corrected phase matrices for the disks, needles, and branches are applied in the single layer random discrete medium where the second order iterative radiative transfer solutions are obtained. Theoretical analyses of the effects of these corrections to the backscattering returns for various volume fractions, frequencies, incident angles, orientations, and sizes are carried out. It is found that the array phase correction is important for an electrically dense medium, whereas the amplitude and the Fresnel phase corrections are required when the frequency increases and enters into the Fresnel region. Good agreements are obtained from the comparisons of the theoretical predictions with the multifrequency and multipolarization measurement results of the Japanese cypress and boreal forest.